Peran Struktur Keluarga dalam Membentuk Perilaku Remaja - Puspita, Rezka; Satriah, Lilis; Lukman, Dede (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2023)
This study aims to examine the form of family interaction, the function of the family subsystem, and the rules of the family system on the families of students involved in juvenile delinquency at Al-Hadi High School in Bandung as a basic in creating Islamic Counseling guidance programs with a family approach at school. The research method use in this study is a qualitative method with a Case Study approach. The results of the study indicate that juvenile delinquency behavior that occurs is caused by a malfunctioning structure in the student’s family. The absence of interaction patterns in the family, the function of the family sub-system is not working, the existence of disputes between family members, and the absence of rules in the family are factors students are involved in juvenile delinquency behavior. From the four families of students who have been examined it can be conclude that, the busyness of parents to search for material, lack of attention and supervision, also the lack of religious practice or moral guidance becomes a problematic impact on the dysfunction of each subsystem in the family. Giving rise to problems or symptoms in family members.